Khuluqiyah Values in Sedekah Pedusunan in Strengthening Character Based on Local Wisdom - Elhefni, Elhefni; Al Ihwanah, Al Ihwanah; Syarifudin, Ahmad; Handayani, Tutut; Ariani, Rita (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
Local culture is increasingly marginalized, even though it needs to be preserved as an identity because it has many values. This research analyzes Sedekah Pedusunan in strengthening character based on local wisdom. This research uses qualitative methods with an ethnographic design. Data was collected through interviews and observations. Data analysis uses domain analysis techniques, taxonomic analysis, componential analysis, and cultural theme analysis. This research found that this Sedekah Pedusunan is an activity based on culture and rules established by society because culture itself results from a long process through history. The local wisdom of Sedekah Pedusunan is carried out to reject balak and pray for the spirits of ancestors, given for the blessings that have been obtained. Sedekah Pedusunan is carried out in five stages, namely the 1) deliberation stage, 2) the begerai stage (fund collection), 3) the cleaning stages, 4) the implementation stages; and 5) the besekum stage (asking for blessings). The khuluqiyah values in Sedekah Pedusunan include helping, respecting other people's opinions, compassion, gratitude, politeness, forging cooperation, discipline, keeping promises, honesty, responsibility, upholding morals towards neighbors, and acting good to anyone. With khuluqiyah values, it is hoped that community members can live in harmony and peace and continue to preserve local wisdom culture. With this research, it is hoped that the Sedekah Pedusunan will be preserved as an identity.